Centros de serviços compartilhados: estudo de caso sobre o processo de implantação - Martins, Vicente de Paula (2008)
The implementation and expansion of the shared services has taken prominent place in the current strategy of many corporations. This demonstrates the value and the success of an organizational model which presents as main advantages the reduction of costs and improvements on services for support and administrative processes. This dissertation will describe the implementation process used by a focal company we based on to develop this case study, we also make an analysis of the most critical points identified on the implementation process